2022
DOI: 10.1002/bies.202100060
|View full text |Cite
|
Sign up to set email alerts
|

New tools suggest a middle Jurassic origin for mammalian endothermy

Abstract: We suggest that mammalian endothermy was established amongst Middle Jurassic crown mammals, through reviewing state-of-the-art fossil and living mammal studies. This is considerably later than the prevailing paradigm, and has important ramifications for the causes, pattern, and pace of physiological evolution amongst synapsids. Most hypotheses argue that selection for either enhanced aerobic activity, or thermoregulation was the primary driver for synapsid physiological evolution, based on a range of fossil ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 122 publications
(285 reference statements)
1
12
0
Order By: Relevance
“…We emphasize that our methodology and data were chosen to provide a biologically meaningful framework for our specific question. We confirm that these methods are valid and support our conclusion that the fossil mammaliaforms Morganucodon and Kuehneotherium had both basal and maximal metabolic rates outside the range of modern mammals, and that full modern mammalian endothermy had yet to evolve in the Early Jurassic 1 , 12 .…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…We emphasize that our methodology and data were chosen to provide a biologically meaningful framework for our specific question. We confirm that these methods are valid and support our conclusion that the fossil mammaliaforms Morganucodon and Kuehneotherium had both basal and maximal metabolic rates outside the range of modern mammals, and that full modern mammalian endothermy had yet to evolve in the Early Jurassic 1 , 12 .…”
Section: Discussionsupporting
confidence: 85%
“…These authors 19 , 20 suggested further that high metabolic rates, endothermy and ossified respiratory turbinals were all lacking in Morganucodon and closely related mammaliaforms. More generally, our reason for citing these varied studies was to show the wide range of times suggested for the origin of mammalian endothermy with different methods and the reinterpretation of many of the characters previously associated with endothermy 1 , 21 (and see Newham et al 12 ).…”
Section: Discussionmentioning
confidence: 99%
“…What does clearly distinguish the two clades of endothermic amniotes from each other and from the ectothermic amniotes is the distribution of numbers of neurons across brain structures. Considering the shared relationships in the light of evidence that stem amniotes were ectothermic (Newham et al, 2022), it is parsimonious to postulate that the scaling rules that apply across brain structures in modern reptiles are conserved from stem amniotes. In this case, birds appeared with a 3-fold step increase in numbers of neurons in the cerebellum for every neuron in the rest of brain compared to the closest living non-avian reptilian relatives, turtles and crocodiles (Figure 6).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Rezende et al (2020) argued that endothermy emerged in birds only with the extreme miniaturization that took place in the paravian lineage in the Middle and Late Jurassic, 175 Ma. Similarly, Newham et al (2022) identify a late origin of endothermy in mammals also in the Middle Jurassic. Grigg et al (2022) argue for a single origin of endothermy in early amniotes from physiological and paleontological evidence.…”
Section: Origins Of Endothermymentioning
confidence: 92%
“…Similarly, Newham et al (2022) point to the Middle Jurassic as the time of origin of endothermy in mammals, long after the emergence of indicators accepted by other authors (e.g., Botha-Brink et al, 2018;Benton, 2021) as evidence for earlier origins, whether in the Middle or Late Permian (separation of lumbar and thoracic regions and origin of diaphragm; differentiation of dentition; bony secondary palate; enlargement of brain), Early Triassic (parasagittal gait; nutrient foramina on snout suggesting muscular lips and hair; parental care; fibrolamellar bone; reduced red blood cell size), or Late Triassic (neurosensory evolution and hair; miniaturization on mammalian lineage; ossified nasal turbinates). Newham et al (2022) acknowledge all these features and their relative timings of origin but argue that they indicate modifications to locomotory mode and enhanced aerobic activity, but not endothermy. They emphasize the importance of the acquisition of both a high basal metabolic rate (BMR) and a high maximum metabolic rate (MaMR), both of which are features of modern mammals.…”
Section: Origins Of Endothermymentioning
confidence: 98%